Perancangan Interior Pusat Fashion Lokal “Indonesian Fashion Chamber” di Surabaya - Vonna Vania Winardy; Sriti Mayang Sari; Celine Junica Pradjonggo (Intra, 2018)
Surabaya is currently developing the creative fashion industry. In order to accommodate fashion people, an organization called Indonesian Fashion Chamber (IFC) was established in 2015. IFC has created many creative programs and activities, and also contribute to small business (UKM) development in Surabaya. However, IFC has not had a permanent facility that could accommodate all their activities. Therefore, it is necessary to design a local fashion center "Indonesian Fashion Chamber" that intend to maximize facilities for fashion activity and bring more benefits to various parties. The design concept is "Idyllically Flexible in Character", which aim to create a beautiful, simple, and natural design, that focuses on design's flexibility in doing changes or adjustments to various activities while sticks to the characteristics of IFC.